(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2019)
With the present scenario of continuous globalization and industrialization, quality is one of the objectives of the service industry to survive in this competitive world. The valuable contribution of the educational institution as a service industry is remarkably significant in developing our country. As state universities and colleges perform their mandates along instruction, research, and extension including production must serve their clients with quality and excellence. Without the provision of quality, state universities usually do not survive because they will not be able to attract their primary clients which are the students to patronize their service. There is a need, then, for all the State Universities and Colleges offering business administration courses to continue improving their facilities, service, and qualifications of their faculty members. The study assessed the Quality Management Practices of the State Universities in the Ilocos Region Offering the Business Administration Program. The descriptive method of research was used in this study using the questionnaire as the main data gathering instrument in the assessment of the quality management practices of the state universities in the Ilocos Region. The data were drawn from the four (4) State Universities in the Ilocos Region offering the business administration. Descriptive statistics were used to analyze and interpret the data of this study. The study found out that a great number of BSBA faculty teaching across SUC’s are highly qualified, well-trained and experienced and imbued with great characteristics and caliber in providing outstanding services to the program and the students as the business partners. The professional profile of the SUC’s in the Ilocos Region offering the BSBA Program had not consistently satisfied the standard requirements and implementation instituted by the AACCUP, Inc. except VMGO, Extension, and Community Development and Library Services. And the groups of BSBA faculty consistently experienced the value of high esteem in putting into service the quality management practice of the SUC’s in the Ilocos Region along with the seven indicators of management practices than the groups of students. The standard or quality of an institution like the state university is greatly measured by the qualifications of its faculty. In this light, the faculty should be composed of competent members in terms of academic qualifications, experience, and professional expertise.